A new and unusual Digonocryptus Viereck (Hymenoptera, Ichneumonidae,Cryptinae), with notes on two other rare species - Supeleto, Fernanda A.; Aguiar, Alexandre P. (Zootaxa, 2023)
Digonocryptus magnus sp. nov., from French Guyana, is described and illustrated, and new records, morphological and morphometric data are presented for two other rare species, D. coloratus (Szépligeti, 1916), registered for the first time from Colombia, and D. zatheos Aguiar & Santos, 2012. The new species is characterized by having the apical margin of the clypeus straight, medially with a small tooth, propodeal apophyses stout, scale-shaped, fore wing with ramellus, areolet about as wide as high, nearly quadrate, 2r-m as long as the mostly spectral 3r-m, T1basally with a distinct lateral rounded flange, and the longest ovipositor of the genus. The study employs morphological character coding combined with a reanalysis of published molecular data to investigate the phylogenetic placement of D. magnus. The results suggest that it may represent a borderline species within Digonocryptus or potentially a new genus, although further investigation is required due to limited available material and inconclusive data.